2018
DOI: 10.1002/anie.201802452
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptides with High Zwitterion Density for Safe and Effective Therapeutics

Abstract: The commonly used "stealth material" poly(ethylene glycol) (PEG) effectively promotes the pharmacokinetics of therapeutic cargos while reducing their immune response. However, recent studies have suggested that PEG could induce adverse reactions, including the emergence of anti-PEG antibodies and tissue histologic changes. An alternative stealth material with no or less immunogenicity and organ toxicity is thus urgently needed. We designed a polypeptide with high zwitterion density (PepCB) as a stealth materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…Synthesis and Self-Assembly of POEGMA-b-P(MAA-co-VSPpaMA) Block Copolymer Thes ynthesis of POEGMA-b-P(MAA-co-VSPpaMA) block copolymer is illustrated in Schemes S1 and S2 in the Supporting Information. Theb iocompatible POEGMA [23] was first prepared by RAFT polymerization of OEGMA, and then tBMA was selected as the second monomer to prepare POEGMA-b-PtBMA block copolymer by using POEGMA as the macro-RAFT agent. Gel permeation chromatography (GPC,S upporting Information, Figure S1) and 1 [24] to produce VSPpa-OH by Steglich esterification, and then VSPpa-OH was further conjugated to the POEGMA-b-PMAA block copolymer to obtain the 1 O 2responsive POEGMA-b-P(MAA-co-VSPpaMA) block copolymer (denoted VSP).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and Self-Assembly of POEGMA-b-P(MAA-co-VSPpaMA) Block Copolymer Thes ynthesis of POEGMA-b-P(MAA-co-VSPpaMA) block copolymer is illustrated in Schemes S1 and S2 in the Supporting Information. Theb iocompatible POEGMA [23] was first prepared by RAFT polymerization of OEGMA, and then tBMA was selected as the second monomer to prepare POEGMA-b-PtBMA block copolymer by using POEGMA as the macro-RAFT agent. Gel permeation chromatography (GPC,S upporting Information, Figure S1) and 1 [24] to produce VSPpa-OH by Steglich esterification, and then VSPpa-OH was further conjugated to the POEGMA-b-PMAA block copolymer to obtain the 1 O 2responsive POEGMA-b-P(MAA-co-VSPpaMA) block copolymer (denoted VSP).…”
Section: Resultsmentioning
confidence: 99%
“…MON‐DN@PCBMA were fabricated by a modified reflux‐precipitation polymerization method . In a typical route, 20 mg of MON‐DN, 95 mg of CBMA monomer, 4 mg of AIBN, 5 mg of BAC, and 40 mL of acetonitrile were mixed and stirred at 90 °C for 1 h under an atmosphere of N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, surface coating of a zwitterionic polymer may increase the blood circulation of nanoplatforms. However, the currently used zwitterionic polymer coatings are mainly concentrated on linear zwitterionic polymer chains, which might not be enough to conceal the nanoparticle surface completely . Benetti and co‐workers found that small plasma proteins such as bovine serum albumin (BSA), can physisorb on linear brush shells composed of poly‐2‐ethyl‐2‐oxazoline (PEOXA).…”
Section: Introductionmentioning
confidence: 99%
“…After 24 and 72 h, free uricase underwent rapid clearance from circulation, while the uricase-modified PepCB and PEGylated uricase showed sustained activity, with the uricase-modified PepCB achieving the longest half-life. This phenomenon was likely due to the stronger hydration effect of carboxybetaine groups in comparison to ethylene glycol units, highlighting the advantageous properties of zwitterionic PepCB over conventional PEG [79].…”
Section: Zwitterionic Polymersmentioning
confidence: 99%
“…The authors concluded that zwitterionic materials, as the next generation of biomaterials, open new avenues for the design and synthesis of anti-fouling agents for therapeutic drug delivery. Zhang et al interrogated an alternative stealth material consisting of polypeptides with a high zwitterion density (PepCB) (Figure 8a) by utilizing uricase as a model protein to examine the different pharmacokinetic and immunological profiles of uricase-modified PepCB and PEGylated uricase in rats in vivo [79]. After 24 and 72 h, free uricase underwent rapid clearance from circulation, while the uricase-modified PepCB and PEGylated uricase showed sustained activity, with the uricase-modified PepCB achieving the longest half-life.…”
Section: Zwitterionic Polymersmentioning
confidence: 99%